Development of converted nearfield acoustic holography method (The verification by experiments using mechanical elements) - Masao NAGAMATSU (Nihon Kikai Gakkai ronbunshu, 2015)
There are several types of sound localization methods. However, the almost methods are used for sound localization of middle frequency noise around 1kHz. In high frequency, the measurement of sound field needs huge load. Therefore the measurement of high frequency noise by sound localization methods is unrealistic. We are currently developing the Converted Nearfield Acoustic Holography method, which is converted method of conventional Nearfield Acoustic Holography method. This method can localize the high frequency noise source with few quantity of datum. Therefore the load in measurement is quite light. In this paper, the noise of a gear set and a linear slider are measured as examples of application of the Converted Nearfield Acoustic Holography method to the actual industrial elements. As a result, since this method has some deterioration of resolution in the reconstructed image, this method can localize high frequency noise source with quite quick measurement.